Correlation of Neutrophil-Lymphocyte Ratio, Alpha-Fetoprotein, and PIVKA-II with Staging of HCC Related HBV at Dr. Mohammad Hoesin Hospital, Palembang - Rahmayani, Febry; Suyata, Suyata; ., Legiran (The Indonesian Society for Digestive Endoscopy, 2025)
Background: The staging of Hepatocellular carcinoma (HCC) requires evaluating the tumor size and number, liver function, physical performance, tumor invasion, extrahepatic metastasis, and clinical symptoms. Biomarkers such as neutrophil-lymphocyte ratio (NLR), alpha-fetoprotein (AFP), and protein induced by the absence of vitamin K or antagonist-II (PIVKA-II) have been identified as valuable diagnostic and prognostic tools for HCC. This study aims to investigate the correlation between NLR, AFP, and PIVKA-II and HCC stages.Methods: This observational study was conducted at the Department of Internal Medicine, Dr. Mohammad Hoesin Hospital, Palembang, from April to July 2024. HCC stages were classified using the Barcelona Clinic Liver Cancer (BCLC) system. NLR, AFP, and PIVKA-II levels were measured using ELISA method. Data were analyzed susing one-way ANOVA or the Kruskal-Wallis test.Results: A total of 38 patients with HCC who met the inclusion criteria were included in the study. There was a weak positive correlation between NLR and HCC stage (r = 0.334; p = 0.040), a moderate positive correlation between AFP and HCC stage (r = 0.499; p = 0.001), and a strong positive correlation between PIVKA-II and HCC stage (r = 0.797; p = 0.000). PIVKA-II and AFP were found to have a significant sequential effect on the BCLC stage.Conclusion: PIVKA-II and AFP are significant indicators for assessing BCLC stages, offering valuable support for the diagnosis and management of HCC.